A Recombinant Acetylcholine Receptor α1 Subunit Extracellular Domain Is a Promising New Drug Candidate for Treatment Of Myasthenia Gravis - Lazaridis, Konstantinos; Fernandez-Santoscoy, Maria; Baltatzidou, Vasiliki; Andersson, Jan-Olof; Christison, Richard; Grünberg, John; Tzartos, Socrates; Löwenadler, Björn; Fribert, Charlotte (Frontiers in Immunology, 2022)
Background and Aims Myasthenia gravis (MG) is a T-cell dependent antibody-mediated autoimmune disease in which the nicotinic acetylcholine receptor (AChR) is the major autoantigen, comprising several T and B cell auto-epitopes. We hypothesized that an efficacious drug candidate for antigen-specific therapy in MG should comprise a broad range of these auto-epitopes and be administered in a noninflammatory and tolerogenic context. Methods We used a soluble mutated form of the extracellular domain of the α1 chain of the AChR (α1-ECDm), which represents the major portion of auto-epitopes involved in MG, and investigated, in a well-characterized rat model of experimental autoimmune myasthenia gravis (EAMG) whether its intravenous administration could safely and efficiently treat the autoimmune disease. Results We demonstrated that intravenous administration of α1-ECDm abrogates established EAMG, in a dose and time dependent manner, as assessed by clinical symptoms, body weight, and compound muscle action potential (CMAP) decrement. Importantly, the effect was more pronounced compared to drugs representing current standard of care for MG. The protein had a short plasma half-life, most of what could be recovered was sequestered in the liver, kidneys and spleen. Further, we did not observe any signs of toxicity or intolerability in animals treated with α1-ECDm. Conclusion We conclude that intravenous treatment with α1-ECDm is safe and effective in suppressing EAMG. α1-ECDm is in preclinical development as a promising new drug candidate for MG.